City life on fast lanes: Urbanization induces an evolutionary shift towards a faster lifestyle in the water flea Daphnia. (28th August 2018) - Brans, Kristien I.; De Meester, Luc
Abstract: Multiple species show significant trait shifts in response to urbanization. Yet, the impact of anthropogenic warming linked to the urban heat island effect is remarkably understudied. In addition, the relative contributions of phenotypic plasticity and genetic change underlying trait shifts in response to urbanization are poorly known. A common garden study with the water flea Daphnia magna revealed that both genetic differentiation in response to urbanization and phenotypic plasticity in response to higher rearing temperature (24°C) induced significant parallel multivariate shifts in life‐history strategy along the slow–fast pace‐of‐life axis. Urban animals and animals reared at higher temperatures are characterized by fast maturation, early release of progeny, a smaller size at maturity, increased fecundity and higher performance (given by maximal population growth rate " r ") compared to genotypes isolated from rural ponds and animals reared at lower temperatures, respectively. Evolution in response to urbanization accounted for 30% of the total observed shift in life history and caused a significant change in mean trait values, while plasticity responses to experimental warming were unaltered between urban and rural populations. The total trait change achieved through both plasticity and evolution ranged from 8% to 56% depending on the trait. Our results provide clear evidence for evolution underlying an increase in pace of life of populations in response to urbanization. Given the pivotal role of Daphnia in aquatic ecosystems, this shift potentially feeds back to population structure, top‐down control of algae and food web dynamics in urban freshwater ecosystems. In addition, we argue that adaptation to urban heat islands might render these populations preadapted in a context of future climate change. plain language summary is available for this article. Abstract : Plain Language Summary